A framework proposal for resilience assessment in traditional commercial centres: case of the historical bazaar of bursa as a resilient world heritage site - Havva Tlemsani Bozdağ; Rachida Benabbou; Tulin Vural Arslan (Heritage Science, 2022)
Abstract Throughout history, the different cycles of change that traditional commercial centres (bazaars) have undergone in different Islamic cities call attention to the hidden abilities insuring their resilience until today. To understand the way in which these bazaar areas absorb and adapt to change, this paper investigates the resilience awareness of a specific case study ‘the bazaar of Bursa’, by dealing with key morphological, behavioural and institutional aspects. Several resilience assessment frameworks have been developed, including cultural, economic, and spatial proxies. However, most of them have focused on physical structures while assessing resilience concretely. This study represents a first step towards a Framework Proposal for resilience assessment in traditional commercial centres (bazaars) combining together tangible and intangible features specific to the historical bazaar of Bursa as a case study using a quantitative approach in a form of a survey. The findings showed a clear overlap between the tradesmen’s perception of factors affecting resilience in the bazaar of Bursa and those proposed by authors. This research may help decision-makers gain a better understanding of the key hidden factors promoting resilience in such historical urban fabrics and guide them in making adequate planning decisions in the future.